The use of RAPD for identifying and classifying Musa germplasm - Howell, E.C.; Newbury, H.J.; Swennen, Rony L.; Withers, Lyndsey A.; Ford-Lloyd, B.V. (Canadian Science Publishing, 1994)
Using the technique of random amplified polymorphic DNA (RAPD), we have identified 116 amplification products in Musa germplasm using nine primers. This has enabled us to identify RAPD markers that are specific to each of nine genotypes of Musa representing AA, AAA, AAB, ABB, and BB genomes. The pattern of variation observed following the application of multivariate analyses to the RAPDs banding data is very similar to the pattern of variation defined using morphological characters and used to assign Musa material into the different genome classes.